Artificial rearing of baby pigs with twice-a-day feeding and cow colostrum - M T Noll; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1979)
Four experiments involving 140 pigs were conducted to evaluate cow colostrum and twice-a-day feeding in artificial rearing of baby pigs. Piglets were allowed to nurse the sow for 15 hours after birth and allotted by litter and weight to milk replacer or milk replacer plus cow colostrum. Piglets were housed in individual wire cages and fed four times on day one, three times on day two, and twice daily days 3 through 21. Dry feed was offered to pigs after day 14. Pigs were removed from the individual cages and moved to a conventional nursery at 21 days of age. Piglets receiving cow colostrum had improved weight gains and decreased incidence of scours during the first week of life. Piglets fed cow colostrum had increased livability (98 vs. 91%) compared to piglets receiving only milk replacer. There was little advantage to feeding cow colostrum after the first week. Piglets raised artificially were similar in weight to sow-reared pigs at 6 weeks of age. These results suggest a practical, inexpensive method of artificially rearing of orphaned or extra baby pigs.; Swine Day, Manhattan, KS, November 8, 1979
Keywords: Swine day; 1979; Kansas Agricultural Experiment Station contribution; no. 80-136-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 371; Swine; Artificial rearing; Cow colostrum